4(2x+3)-24=

Simple and best practice solution for 4(2x+3)-24= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4(2x+3)-24= equation:


Simplifying
4(2x + 3) + -24 = 0

Reorder the terms:
4(3 + 2x) + -24 = 0
(3 * 4 + 2x * 4) + -24 = 0
(12 + 8x) + -24 = 0

Reorder the terms:
12 + -24 + 8x = 0

Combine like terms: 12 + -24 = -12
-12 + 8x = 0

Solving
-12 + 8x = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '12' to each side of the equation.
-12 + 12 + 8x = 0 + 12

Combine like terms: -12 + 12 = 0
0 + 8x = 0 + 12
8x = 0 + 12

Combine like terms: 0 + 12 = 12
8x = 12

Divide each side by '8'.
x = 1.5

Simplifying
x = 1.5

See similar equations:

| 40=w(w-3) | | -10+4n=6(n-2) | | 128=3.14+8 | | 2=In(x+7) | | 5x+17=6x-1 | | 13=n-(-5) | | 6(1+6x)=5x-25 | | 243x+2=9x | | 8.4-b=17.1 | | 128=3.14(8) | | 4x-(x-3)=6 | | 5x+5=41+x | | X-5=-5x-11 | | -3x+5(-x+6)=-10 | | v-1=2(-5-4v) | | z^2+(-1-2i)*z-6+6i=0 | | X-5=-(5x+11) | | tg^2x=0 | | X+sqrt(3)+3x=18-2x | | 15.4*4.75= | | 6c-3-2c=4c+4-0 | | -6+3(1+v)=5+5v | | (a-2b)(a+2b)=45 | | -b^2-9= | | 420-3x=4x | | 4xn+11=27 | | 60x=5x+1 | | 2[2x-1]=-14 | | 1x+9=16 | | 0.125(6+x)=8 | | 2[2x-1]=14 | | 5(b-5)=-15-5b |

Equations solver categories